Engineered immune cell therapies for solid tumors: pharmacological advances, clinical outcomes, and future directions - Althafar, Ziyad M. (Frontiers in Pharmacology, 2025)
Solid tumors, accounting for around 90% of human cancers, present unique challenges due to antigen heterogeneity, immunosuppressive microenvironments, and limited accessibility for conventional pharmacotherapies. Immunotherapies, particularly engineered immune cell therapies, exploit the immune-tumor interplay, offering novel pharmacological strategies for solid malignancies. Genetic engineering enhances adoptively transferred cells, such as T cell receptor therapy, chimeric antigen receptor (CAR)-T cells, tumor-infiltrating lymphocytes (TILs), natural killer cells, and CAR-macrophages, by optimizing their targeting and effector functions. Clinically, TIL delivery has shown significant responses in advanced melanoma, with lifileucel gaining United States FDA approval as a pioneering TIL therapy for solid tumors. Ongoing trials further explore these approaches, revealing promising outcomes in overcoming immunosuppressive barriers. However, challenges persist, including optimizing combination therapies, streamlining manufacturing for off-the-shelf accessibility, and mitigating pharmacotoxicity. This review synthesizes recent advances in engineered immune cell therapies for solid tumors, emphasizing their pharmacological mechanisms, clinical efficacy, and translational potential. By addressing current hurdles, such as enhancing tumor penetration and minimizing adverse effects, this article outlines future directions to refine these therapies as safe, effective pharmacological tools in oncology.